Effect of different types of aerobic exercises on cancer-related fatigue among colorectal cancer patients: a meta-analysis based on randomized controlled trials - Xiaoyang, Xu; Chunhui, Zhou; Xiaolan, Yang; Dong, Zhu (BMC cancer, 2025)
Background Colorectal cancer (CRC) is a prevalent and lethal disease. Cancer-related fatigue (CRF) poses a significant challenge to patients during their daily life and rehabilitation. Research indicates that aerobic exercises can alleviate CRF, but the optimal type, intensity, and timing of exercise interventions remain unclear. Aim To conduct a meta-analysis of randomised control trials comparing the effects of different aerobic exercise intensities and training protocols on CRF and HRQoL. Method This meta-analysis searched electronic databases, including PubMed, Web of Science, Embase, and Cochrane Library, from their inception until February 2024. The meta-analyses were conducted using Revman 5.3 software. It examined the effects of different types of aerobic exercises on CRF among CRC patients. Results Ultimately, 9 studies were included with a total of 425 patients. The meta-analysis results showed that aerobic exercises significantly reduce symptoms of CRF (SMD = − 0.35, Z = 2.39, P = 0.02), with continuous and interval training presenting the most promising type. The intensity and type of exercise influence CRF outcomes. The analysis also revealed potential publication bias in CRF research, suggesting the need for more studies that include negative results. Conclusion These findings underscore the importance of personalized exercise prescriptions and integrating exercise into cancer care to improve CRF and enhance patients’ quality of life. Further research is necessary to explore the best exercise regimens and their long-term effects.